Study of the Nucleation and Growth Mechanisms of Copper Electrodeposition on Bare and Nitrogen-Doped Reduced Graphene Oxide Modified SnO2:F/glass Substrates. Issue 12 (2nd September 2020) - Riveros, G.; León, M.; Ramírez, D.; Hernández, L.; Martín, F.; Romero, R.; Dalchiele, E. A.
Abstract : In this article, the influence of a nitrogen-doped electrochemically reduced graphene oxide layer on the nucleation and growth mechanisms of copper electrodeposition was studied. Thus, copper electrodeposition from an acidic solution was evaluated using two different substrates: fluorine-doped tin oxide (FTO), and fluorine-doped tin oxide covered with a nitrogen-doped reduced graphene oxide layer (FTO/N-ERGO). In both cases, chronoamperometric curves were obtained, which were analyzed and deconvoluted using pre-established models and equations, where the different contribution and nucleation parameters were determined. Field emission scanning electron microscopy (FESEM) images were acquired in order to observe the morphology and verify the nuclei density for each case considered in this study. In the case of copper electrodeposition onto FTO, an instantaneous three-dimensional nucleation was observed, together with a proton reduction reaction. When FTO/N-ERGO was used as a substrate, a new instantaneous two-dimensional nucleation process was observed in addition to the processes previously described. Furthermore, the increased density of active sites and the changes in copper morphology are directly related with the N-ERGO layer, which also increased the kinetic constant for the proton reduction reaction and the nucleation rate per active site during the copper electrodeposition process.